2003
DOI: 10.1016/s1525-1578(10)60461-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Genotyping of Common MeCP2 Mutations with an Electronic DNA Microchip Using Serial Differential Hybridization

Abstract: Rett syndrome is a neurodevelopmental disorder that affects females almost exclusively, and in which eight common point mutations on the X-linked MeCP2 gene are knows to cause over 70% of mutation-positive cases. We explored the use of a novel platform to detect the eight common mutations in Rett syndrome patients to expedite and simplify the process of identification of known genotypes. The Nanogen workstation consists of a two-color assay based on electric hybridization and thermal discrimination, all perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…This lowers the cost per SNP to almost one-third of the cost of using a new microelectronic chip and more lowers the cost compared with RFLP analysis by more than one-half. This is approximately the same cost reported by others for detecting eight SNPs on one test site simultaneously (€1.62 per SNP) (6 ). It should be noted, however, that purchase of the Nanogen NMW 1000 Nanochip Molecular Biology Workstation is not included in these calculations.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…This lowers the cost per SNP to almost one-third of the cost of using a new microelectronic chip and more lowers the cost compared with RFLP analysis by more than one-half. This is approximately the same cost reported by others for detecting eight SNPs on one test site simultaneously (€1.62 per SNP) (6 ). It should be noted, however, that purchase of the Nanogen NMW 1000 Nanochip Molecular Biology Workstation is not included in these calculations.…”
supporting
confidence: 68%
“…Other studies have also shown the multiplexing ability of the microelectronic chip by analyzing eight different SNPs on one test site simultaneously (6 ). Furthermore, compared with other microarray systems, the microelectronic chip allows simultaneous use of a wide variety of probes of different lengths and chemical compositions on the same chip.…”
mentioning
confidence: 99%
“…With well designed assays, including multiplex PCR, multiple addressing of uniplexed PCR-products to the same pad, or serial hybridization of reporters (involving intermediate stripping of previously hybridized reporters) ( Figure 1) (16,18,(23)(24)(25), costs per sample for nine β-globin mutations range between €5-8, including sample preparation and PCR amplification. A recently updated version of the platform (NanoChip 400; Nanogen Inc.) includes 400 pads per cartridge that can be scanned in a single day, further facilitating large-scale screening applications.…”
Section: Costsmentioning
confidence: 99%
“…A serial hybridization format was performed by chemically stripping previously hybridized reporters (NaOH 0.1N) for 3 min [Frusconi et al, 2004;Thistlethwaite et al, 2003]. Amplicons were subjected to 24 subsequent hybridization steps, with all different sets of reporters specific for the 24 mutations.…”
Section: Serial Reporter Hybridizationmentioning
confidence: 99%